Regulatory Mechanisms of bHLH Transcription Factors in Plant Adaptive Responses to Various Abiotic Stresses - Qian, Yuchen; Zhang, Tongyao; Yu, Yan; Gou, Liangpeng; Yang, Jingting; Xu, Jia; Pi, Erxu (Frontiers in Plant Science, 2021)
Basic helix-loop-helix proteins (bHLHs) comprise one of the largest families of transcription factors (TFs) in plants. They have been shown to be involved in responses to various abiotic stresses, such as drought, salinity, chilling, heavy metal toxicity, iron deficiency, and osmotic damages. By specifically binding to cis-elements in the promoter region of stress related genes, bHLHs can regulate their transcriptional expression, thereby regulating the plant’s adaptive responses. This review focuses on the structural characteristics of bHLHs, the regulatory mechanism of how bHLH are involved transcription activation, the crosstalk between bHLHs and hormones, and the mechanism of how bHLH regulate the transcription of target genes under various stresses. Finally, as increasing research demonstrates that flavonoids are usually induced under fluctuating environments, the latest research progress and future research prospects are described on the mechanisms of how flavonoid biosynthesis is regulated by bHLHs in the regulation of the plant’s responses to abiotic stresses.